BIOCE - Bayesian inference of protein conformational ensembles from limited structural data - Potrzebowski, Wojciech (SciLifeLab Serve, 2026)
A method based on Bayesian statistics that infers conformational ensembles from a structural library generated by all-atom Monte Carlo simulations. The first stage of the method involves a fast model selection approach based on variational Bayesian inference that maximizes the model evidence of the selected ensemble. This is followed by a complete Bayesian inference of population weights in the selected ensemble.